Issues and Challenges of Student Financing Systems in Africa: The Case of Tanzania - Kossey, Masumbuko Mathew; Ishengoma, Johnson Muchunguzi (International Journal of African Higher Education, 2017)
This article investigates the challenges confronting student fnancing systems in Africa, with specifc reference to Tanzania’s Higher Education Students’ Loans Board (HESLB). It shows that the major challenges include limited resources, unemployment among loan benefciaries, increased loans applications, the lack of a national identifcation system, emigration of loan benefciaries, poor policy and legal frameworks, and corruption among HESLB staﬀ and loan benefciaries. The article recommends that the HESLB should diversify its sources of funding to reduce dependence on government; enforce loan repayment through legislation that enables direct reimbursement from benefciaries’ salaries; charge interest higher than the inﬂation rate; and embark on aggressive public education campaigns on the importance and benefts of the loan scheme and loan repayments. Cet article examine les défs auxquels sont confrontés les systèmes de fnancement de l’enseignement supérieur en Afrique, en prenant pour exemple le Comité de Prêts pour Etudiants de l’Enseignement Supérieur de Tanzanie (HESLB). Il montre que les défs principaux sont liés au manque de ressources et au chômage des bénéfciaires de prêts, à une augmentation des demandes de prêts, à l’absence d’un système d’identifcation national, à l’émigration des bénéfciaires de prêts, à l’inadaptation des politiques et des cadres légaux, et à la corruption du personnel de l’HESLB et des bénéfciaires de prêts. Cet article recommande que l’HESLB diversife ses sources de fnancement pour limiter sa dépendance vis-à-vis du gouvernement ; qu’il renforce le taux de remboursement des prêts au moyen d’une législation permettant un prélèvement direct sur le salaire des bénéfciaires ; qu’il charge des intérêts plus haut que l’inﬂation ; et qu’il mène une campagne agressive d’éducation du public sur l’importance et les bénéfces du système de prêts et de remboursements pour les étudiants.